Neuroanatomical Quantitative Proteomics Reveals Common Pathogenic Biological Routes between Amyotrophic Lateral Sclerosis (ALS) and Frontotemporal Dementia (FTD) - Marina Oaia Iridoy (International Journal of Molecular Sciences, 2018)
(1) Background: Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are neurodegenerative disorders with an overlap in clinical presentation and neuropathology. Common and differential mechanisms leading to protein expression changes and neurodegeneration in ALS and FTD were studied trough a deep neuroproteome mapping of the spinal cord. (2) Methods: A liquid chromatography tandem mass spectrometry (LC-MS/MS) analysis of the spinal cord from ALS-TAR DNA-binding protein 43 (TDP-43) subjects, ubiquitin-positive frontotemporal lobar degeneration (FTLD-U) subjects and controls without neurodegenerative disease was performed. (3) Results: 281 differentially expressed proteins were detected among ALS versus controls, while 52 proteins were dysregulated among FTLD-U versus controls. Thirty-three differential proteins were shared between both syndromes. The resulting data was subjected to network-driven proteomics analysis, revealing mitochondrial dysfunction and metabolic impairment, both for ALS and FTLD-U that could be validated through the confirmation of expression levels changes of the Prohibitin (PHB) complex. (4) Conclusions: ALS-TDP-43 and FTLD-U share molecular and functional alterations, although part of the proteostatic impairment is region- and disease-specific. We have confirmed the involvement of specific proteins previously associated with ALS (Galectin 2 (LGALS3), Transthyretin (TTR), Protein S100-A6 (S100A6), and Protein S100-A11 (S100A11)) and have shown the involvement of proteins not previously described in the ALS context (Methanethiol oxidase (SELENBP1), Peptidyl-prolyl cis-trans isomerase NIMA-interacting 1 (PIN-1), Calcyclin-binding protein (CACYBP) and Rho-associated protein kinase 2 (ROCK2)).